TINJAUAN HUKUM ISLAM TERHADAP TRADING BITCOIN (Ahkam: Jurnal Hukum Islam, 2023)
The study of Islamic law on bitcoin trading has a high urgency, considering that crypto asset trading is increasing in Indonesia from year to year. One of them is the high level of bitcoin trading. The purpose of this study is to examine Bitcoin transactions in the perspective of Islamic Law. This type of research is a type of library research with a normative legal approach. This research analysis uses descriptive analysis. The results of the research in this problem, according to the view of Islamic law, bitcoin transactions are prohibited because bitcoin buying and selling is said to be ghairu sahih buying and selling which is categorized as invalid because the sale and purchase does not meet the conditions for the validity of buying and selling on the object of the goods (sil'ah). Bitcoin contains elements of gharar, maysir, and dharar as the object of sale and purchase, so it does not fulfill the pillars of sale and purchase, so the law of bitcoin trading is invalid and violates the provisions of Islamic law.